ncompatibility of the capulín (Prunus serotina ssp. capuli (Cav.) McVaugh) as rootstock of the sweet cherry tree (Prunus avium L.) - Guzmán, Felix Alberto; Torres, Magdiel; Herrera, María del Carmen; Nieto, Raúl; Almaguer, Gustavo; López, Javier; Segura, Sergio (Revista Mexicana de Ciencias Agrícolas, 2018)
The capulín (Prunus serotina ssp. capuli (Cav.) McVough 1951) is a subspecies of P. serotina Ehnr. of Mesoamerican origin used mainly as fruit. Although from the 80’s there were reports of a collection of capulín from central Mexico, called San Martín, which showed compatibility with the cherry tree (Prunus avium L.) possibly because it was a diploid capulín, this possible quality had not been the subject of a study that the cherry tree is little cultivated in the country. This situation is changing due to the release of new cherry tree varieties with low winter cold requirements. It returned to the idea of testing the materials of capulines that had been described as possible patterns of the cherry tree given the quality of the first one to adapt to the soils in Mexico and the susceptibility of the traditional rootstocks of the cherry tree to cancer (Dibotryon sp.) or blight of fire (Phytophtora sp.) mainly. In this investigation, remarkable compatibility of the Chapingo capulín with the cherry tree was not found and by looking for the causes analyzing both species by means of flow cytometry we found that the San Martin capulín is tetraploid and not diploid as it was supposed. The above is added to the possible production of phenolic compounds that is common in Prunus, producing a translocalized incompatibility that we observe in most of the grafted plants.
Keywords: Prunus; cytometry; Mexico; propagation